2014
DOI: 10.35799/jm.3.2.2014.5862
|View full text |Cite
|
Sign up to set email alerts
|

Barcode DNA Tumbuhan Pangi (Pangium edule R.) Berdasarkan Gen matK

Abstract: DNA barcoding merupakan suatu teknik yang digunakan untuk mempercepat dan mempermudah proses identifikasi organisme dengan menggunakan potongan gen tertentu. Penelitian ini bertujuan untuk menentukan sekuens DNA barcode tumbuhan pangi berdasarkan gen standar matK dan membandingkannya dengan spesies yang berkerabat dekat di GenBank. DNA total daun pangi diisolasi menggunakan Innuprep plant DNA kit dan berhasil diamplifikasi dengan proses Polymerase Chain Reaction (PCR) menggunakan primer berdasarkan gen matK. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…The result showed that matK sequence is more capable to be a DNA barcode for payus limondok orchid than rbcL sequence. Bangol et al (2014) also…”
Section: Analysis Of Matk and Its Sequences Of Tuntun Anginmentioning
confidence: 97%
“…The result showed that matK sequence is more capable to be a DNA barcode for payus limondok orchid than rbcL sequence. Bangol et al (2014) also…”
Section: Analysis Of Matk and Its Sequences Of Tuntun Anginmentioning
confidence: 97%
“…Therefore, DNA barcoding is carried out to be able to identify quickly and accurately. DNA barcoding is a technique used to speed up and simplify the process of identifying organisms using certain gene fragments (Bangola et al, 2014). DNA barcoding techniques can provide a "biological bar code" from short DNA sequences that are standardized to identify a species (Hajibabaei et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The first flowering time of V. tricolor orchids is relatively long, about five years since seed sowing, therefore, it is difficult to find these orchids in a flowering state in nature [6]. Hence, an alternative identification method is needed other than based on morphological characters, namely DNA barcoding [7].…”
Section: Introductionmentioning
confidence: 99%
“…The matK gene provides high resolution in comparing plant species, but the gene is difficult to amplify. In contrast, the rbcL gene is easy to amplify but has a low resolution so that it is difficult to distinguish species in close relatives [7]. The Internal Transcribed Spacer (ITS) region is a potential barcode originating from the nuclei.…”
Section: Introductionmentioning
confidence: 99%